EVALUASI SISTEM PENGENDALIAN INTERN PENERIMAAN KAS PADA HOTEL LUCKY INN MANADO - Deftrianto, Leonardus I Made; Saerang, David P. E.; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Along with the development era of economic development is very rapid, where the business world is required to try to follow the developments that occur. The object of this research is Hotel lucky inn. The purpose of this study is to find out how the evaluation of internal control system cash receipts at the Hotel Lucky Inn Manado whether it is running effectively or not. The method of analysis used in this study is descriptive analysis is a method of discussion that is describing, describe, compare and explain a data with other data that become benchmarks in this study that is using Mulyadi theory so that it can be drawn conclusions to answer the problem in research studies , and draw conclusions. The results of the research can be seen that the evaluation of internal control system of cash receipt of Hotel Lucky Inn has been effectively seen by fulfilling the elements of internal control. The company's internal control standards are also appropriate.Keywords: Internal Control System, Cash